Songful Handbook. "Handbook of Australian, New Zealand and Antarctic Birds, Volume 6: Pardalotes to Shrike-Thrushes" by P.J. Higgins and J.M. Peter (eds). [review] - Menkhorst, Peter (Australian Book Review, 2003)
The "Handbook of Australian, New Zealand and Antarctic Birds" has already become an indispensable tool for anyone with a serious interest in birds of the Australian region. The authority and detail of the text, and the quality and breadth of the illustrations, mean it will remain the primary source of information about the region’s birds for decades. With the completion of Volume 6, the ambitious plans of a few visionaries in 1985 are now close to fruition. I doubt that even they could have imagined that the final product would be so magnificent or so useful. Australia Council, La Trobe University, National Library of Australia, Holding Redlich, Arts Victoria